(The ultimate sticker book) Space (DK Children; New York, 1993)
The Ultimate Space Sticker Book is an exciting interactive guide that explores the wonders of the universe. Featuring over 60 reusable stickers, this book allows readers to create their own cosmic scenes while learning about planets, stars, and space exploration. Accompanied by fun facts and illustrations, it engages young minds in the science of astronomy, making it an entertaining and educational experience for space enthusiasts.